Peran Aktor Dalam Kebijakan Kesehatan Mental Di Era Pandemi Covid 19 - Irfan Sazali Nasution; Ica Khairunissa; Maymira Inory Harahap; Muchlisin Limbong; Nazwa Nadira Siregar; Natasya Dwi Caudya; Putri Radifah Supardi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The COVID-19 pandemic has significantly impacted the mental health of communities worldwide, including in Indonesia. This study aims to explore the role of actors in mental health policy during the pandemic. A qualitative descriptive method was employed, utilizing questionnaires for data collection. Survey results revealed that 63% of respondents experienced anxiety, and 66% experienced depression. The research identifies various key actors, including the government, educational institutions, and healthcare professionals, and provides recommendations for enhancing mental health support. The study concludes that collaboration among actors is crucial for building a responsive and inclusive mental health system in the pandemic era.